The Effect of Google Classroom's Assisted Blended Learning Model on Mathematical Concepts Understanding and Mathematical Dispositions - Clarisa Ayu Oktaviani Clarisa; Farida; Fredi Ganda Putra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This research is motivated by the low ability to understand mathematical concepts and dispositions. This study aimed to determine the effect of the Google Classroom-assisted blended learning model on mathematical concepts understanding and mathematical dispositions. The method in this study was an experiment with a quasi-experimental design, and the design used was a post-test-only control group design. The population in this study were all students in class X at SMK Muhammadiyah 1 Metro. The sampling technique used simple random sampling. The data analysis technique used is the normality test, homogeneity test, and hypothesis testing with MANOVA. Based on the results of the hypothesis test with Manova, a sig value of 0.014 was obtained with a predetermined significant level of 0.05, which means that the sig value 0.05 then rejects H_0AB and accepts H_1AB. So, it can be concluded that using the Google Classroom blended learning model is more effective in mathematical concepts understanding and dispositions than conventional learning models.